National Association for the Advancement of Colored People records - National Association for the Advancement of Colored People; Gilbert Jonas Company; National Association for the Advancement of Colored People. Washington Bureau
Correspondence, memoranda, minutes, reports, itineraries, biographical material, speeches, testimony, writings, annual convention files, legal case files, testimony, legislation, publications, resolutions, policy statements, constitutions, bylaws, charters, contracts, proposals, scripts, financial records, publicity files, manuals, handbooks, songs, awards, certificates, directories, subject files, daily mail sheets, notes, lists, questionnaires, surveys, certificates, awards, flags, photographs, maps, and printed matter.
Each of the nine parts contains Board of Directors files, annual convention files, general office files, branch files, and legal case files. The general office files include papers of executive secretaries and directors including James Weldon Johnson from 1920 to 1931, Walter Francis White from 1931 to 1955, Roy Wilkins from 1955 to 1977, and Benjamin L. Hooks from 1977 to 1993.
Part I (1909-1940, bulk 1919-1939) includes material relating to the founding and organizational development of the Association (NAACP), racial discrimination and segregation, violence against African Americans, race riots, antilynching legislation, Jim Crow laws, the association's first legal cases, the Scottsboro trial, equal treatment of African Americans before the courts, voting rights, education, labor unions, African American soldiers in World War I, interracial marriages, Haiti, peonage, the film Birth of a Nation, the nomination of John Johnston Parker to the U.S. Supreme Court, William E. Borah's presidential candidacy, and the re-emergence of the Ku Klux Klan.
Part II (1910-1955, bulk 1940-1955) includes material on civil rights, discrimination and desegregation in the armed forces, veterans' programs, employment, healthcare, housing, transportation, and education including Brown v. Board of Education. Also includes material on antilynching legislation, voting rights, racial stereotyping in film, television, and radio, wartime riots, legal cases including Brown v. Board of Education, segregation during World Wars I & II, police brutality, labor unions, and labor conditions.
Part III (1909-1965, bulk 1956-1965) includes such topics as civil rights; desegregation of schools; equal access to employment, healthcare, housing, and transportation; voting rights; sit-ins; the fund-raising telethon entitled "Freedom Television Spectacular;" March on Washington for Jobs and Freedom; Freedom Riders; the Mississippi Freedom Democratic Party; and the murder of Mississippi field secretary Medgar Wiley Evers in 1964. Documents relations between the NAACP and other civil rights organizations including the Congress of Racial Equality, Southern Christion Leadership Conference, and Student Nonviolent Coordinating Committee.
Part IV (1965-1975, bulk 1966-1973) documents the broadening of the NAACP's strategy to include the creation of community-based programs. Includes material relating to housing, labor, relief, education, voting rights, civil rights, Africa, the Black Power movement, federal and state agencies and programs, urban riots, Vietnam, the U.S. Supreme Court nomination of Clement F. Haynsworth, Adam Clayton Powell's expulsion from the U.S. House of Representatives, the slaying of Martin Luther King, Jr., and relations with other civil rights organizations.
Part V (1842-1982, bulk 1956-1982) includes records of the NAACP's legal department relating to cases involving discrimination in housing and employment, civil rights, school desegregation, police brutality, the armed forces, voting rights, reverse discrimination, and the disparate sentencing of African Americans.
Part VI (1884-1992, bulk 1967-1978) includes material on the NAACP Image Awards, ghettos, riots, discrimination, housing programs, voter registration campaigns, television, the U.S. Supreme Court nominations of Clement F. Haynsworth and G. Harrold Carswell, and National Association for the Advancement of Colored People v. Claiborne Hardware Co.
Part VII (1964-1995, bulk 1965-1995) consists of records generated by the Gilbert Jonas Company, a public relations firm that for thirty years contracted to raise funds for the NAACP through direct mail campaigns and other means.
Part VIII (1867-1999, bulk 1978-1991) documents leadership conferences including the NAACP Leadership Summit Conference, Chicago, Ill., 1978, the Black Leadership Meeting, New York, N.Y., 1980, the NAACP Emergency Summit, Washington, D.C., 1985, and the NAACP Conference on the Present Crisis, Washington, D.C., 1989. Topics include the NAACP National Conference on Energy, Washington, D.C., 1977, minority economic opportunity, affirmative action, African American relations with Jews, busing, criminal justice, Jesse Jackson's presidential candidacy, U.S. Supreme Court nominations of Robert H. Bork and Clarence Thomas, tobacco industry, urban ghettos, and relocation of NAACP headquarters to Baltimore, Md. Early material includes papers of Walter Francis White.
Part IX (1914-1993, bulk 1950-1991) documents the efforts of the NAACP's Washington Bureau to influence civil rights legislation and monitor enforcement of the laws by federal agencies. Includes material reflecting the directorships of Clarence M. Mitchell, 1950-1978, and Althea T. L. Simmons, 1979-1990.
Microfilm edition of minutes, 1909-1959, available
Microfilm edition of container G15 available
Microfilm edition of selected bulletins, 1916-1949, available
Microfilm edition of containers C62-112 available
Microfilm produced from originals in Manuscript Division.
Library of Congress Motion Picture, Broadcasting, and Recorded Sound Division.
Keywords: Borah, William Edgar, -- 1865-1940.; Bork, Robert H; Brown, Oliver, -- 1918-1961 -- Trials, litigation, etc; Carswell, G. Harrold -- 1919-; Evers, Medgar Wiley, -- 1925-1963.; Griffith, D. W. -- 1875-1948; Haynsworth, Clement F. -- 1912-1989.; Hooks, Benjamin L. -- 1925-2010.; Jackson, Jesse, -- 1941-; Johnson, James Weldon, -- 1871-1938.; King, Martin Luther, -- Jr., -- 1929-1968.; Mitchell, Clarence M. -- 1911-1984.; Parker, John Johnston, -- 1885-1958.; Powell, Adam Clayton, -- 1908-1972.; Simmons, Althea T. L., -- 1924-1990.; Thomas, Clarence, -- 1948-; White, Walter Francis, -- 1893-1955.; Wilkins, Roy, -- 1901-1981.; Topeka (Kan.). -- Board of Education -- Trials, litigation, etc; United States. -- Congress. -- House; United States. -- Supreme Court; United States. -- Supreme Court -- Officials and employees -- Selection and appointment; Claiborne Hardware Co. -- Trials, litigation, etc; Congress of Racial Equality; Ku Klux Klan (1915- ); Mississippi Freedom Democratic Party; National Association for the Advancement of Colored People -- Awards; National Association for the Advancement of Colored People -- Trials, litigation, etc; Southern Christian Leadership Conference; Student Nonviolent Coordinating Committee (U.S.); Birth of a nation (Motion picture); Crisis (New York, N.Y.); Actions and defenses -- Mississippi; Affirmative action programs -- United States; African American veterans; African Americans; African Americans -- Charities; African Americans -- Civil rights; African Americans -- Crimes against; African Americans -- Economic conditions; African Americans -- Education; African Americans -- Employment; African Americans -- Government policy; African Americans -- Health and hygiene; African Americans -- Housing; African Americans -- Legal status, laws, etc; African Americans -- Medical care; African Americans -- Periodicals; African Americans -- Relations with Jews; African Americans -- Segregation; African Americans -- Social conditions; African Americans -- Societies, etc; African Americans -- Suffrage; African Americans in mass media; African Americans in motion pictures; African Americans in radio broadcasting; African Americans in television broadcasting; Anti-racism -- United States; Black power -- United States; Busing for school integration